2005
DOI: 10.1177/0363546504270998
|View full text |Cite
|
Sign up to set email alerts
|

Topical Glyceryl Trinitrate Application in the Treatment of Chronic Supraspinatus Tendinopathy

Abstract: Topical glyceryl trinitrate treatment significantly improved pain scores, range of motion, internal rotation impingement, muscular force, and patient outcomes in patients with supraspinatus tendinopathy. Topical glyceryl trinitrate should be included as part of nonsurgical management of chronic tendinopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
1
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 25 publications
5
99
1
2
Order By: Relevance
“…Nitric oxide, applied using topical nitroglycerin patches, has been shown to improve outcomes in randomized, double-blind, placebo-controlled trials, possibly by enhancing collagen synthesis. [60][61][62] Sclerosant injections have been shown to give at least shortterm benefit, 63 and might provide a rational basis for targeting neovascularization in painful tendinopathy, which might be triggered initially by hypoxia and regulated by levels of endostatin and vascular endothelial growth factor. 64,65 Aging might reduce the ability of tenocytes to remodel and repair lesions, supporting the use of stem-cell therapies that involve the injection of bone-marrow-derived cells into injured or degenerate tendon; this approach is currently being used to treat equine tendinopathy.…”
Section: New Treatments For Tendinopathy and Future Research Directionsmentioning
confidence: 99%
“…Nitric oxide, applied using topical nitroglycerin patches, has been shown to improve outcomes in randomized, double-blind, placebo-controlled trials, possibly by enhancing collagen synthesis. [60][61][62] Sclerosant injections have been shown to give at least shortterm benefit, 63 and might provide a rational basis for targeting neovascularization in painful tendinopathy, which might be triggered initially by hypoxia and regulated by levels of endostatin and vascular endothelial growth factor. 64,65 Aging might reduce the ability of tenocytes to remodel and repair lesions, supporting the use of stem-cell therapies that involve the injection of bone-marrow-derived cells into injured or degenerate tendon; this approach is currently being used to treat equine tendinopathy.…”
Section: New Treatments For Tendinopathy and Future Research Directionsmentioning
confidence: 99%
“…Paoloni et al 11 found a significant pain relief, an increase in ROM of internal shoulder abduction and rotation, and an increase in strength of the external and internal rotator muscles due to a NT treatment. In a double-blind study with 65 patients diagnosed with Achilles tendinitis, NT treatment was used and stretch exercises were carried out, resulting in effective pain relief.…”
Section: Discussionmentioning
confidence: 99%
“…The positions taken during the ROM measurement of each movement are shown in Figure 1. Abduction was assessed with the shoulder in external rotation, 11 whereas antepulsion and retropulsion were examined with the shoulder in neutral rotation position. 14 External and internal rotations were assessed with the elbow fixed at 901 and the shoulder at 901 of abduction.…”
Section: Wuspi and Scim Scoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Within a tendon, vascularity decreases at the point of the tear as compared to its interface on bone [4]. Although no studies have directly proven a causal relationship between increased vascularity and improved rotator cuff healing, a recent randomized prospective clinical trial has demonstrated a topically applied angiogenic factor, glyceryl trinitrate, reduced shoulder pain and stiffness in patients with chronic supraspinatus tendinopathy [29,42].…”
Section: Biology Of Bone-to-tendon Healingmentioning
confidence: 99%